High-strength light-weight building decoration marine mineral composite material

By using abandoned materials such as Xuanwuyan, coal gangs, iron ore dregs, etc., prepare high -strength lightweight building decorative marine mineral composite materials, solve the problem of insufficient strength of existing aluminum alloy materials, and realize the high strength and lightweightness of the marine platform Effect.

CN119371194APending Publication Date: 2025-01-28FUJIAN QUANZHOU LUOJIANG ZHENFENG MOPEI MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411851553.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing 5000 series aluminum alloy materials are insufficient in ships and ship applications and cannot meet the requirements of lightweight development.

Method used

Use waste materials such as Xuanwu Rock, coal gangs, and iron ore dregs to prepare high -intensity and lightweight buildings to decorate marine mineral composite materials through specific raw material composition and firing processes. Specific steps include the mixing of powder and basalt, the suppression of premissions and firing at 1280-1480 ° C.

Benefits of technology

The utilization rate of abandoned resources has been improved, the production cost is reduced, the strength and lightweight effect of the marine platform are ensured, and the finished product rate and size stability of the material is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of mineral composite material preparation, and particularly relates to a high-strength light-weight building decoration marine mineral composite material which comprises the following raw materials: coal gangue, iron ore tailings, calcite, silicon dioxide, aluminum oxide, calcium oxide, barium silicate, magnesium oxide, iron oxide, titanium oxide, potassium oxide, sodium oxide, arsenic oxide and antimony oxide. The raw material composition of the mineral composite material is limited, waste materials such as coal gangue, iron ore tailings and basalt are selected as main raw materials, so that the utilization rate of waste resources is increased, the cost is greatly reduced, the preparation method of the mineral composite material is further limited, a premix is subjected to compression molding and then is fired at 1280-1480 DEG C, and the mineral composite material is obtained. According to the preparation method, the iron ore tailings, the calcite and the coal gangue can be expanded and cracked into smaller particles, so that the shrinkage of the mineral composite material during preparation is balanced, the strength of the prepared ocean platform is ensured, and the effects of light weight, acid resistance, alkali resistance and corrosion resistance can also be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of mineral composite materials, and in particular relates to a method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration. Background Art

[0002] The traditional materials of ships and warships are mainly steel materials. Although steel materials have the advantages of high strength, they are heavy and have poor corrosion resistance, resulting in heavy weight, poor maneuverability, low carrying capacity and high maintenance costs for ships and warships. Aluminum alloys have the advantages of light weight, good formability and corrosion resistance. Using aluminum alloy materials to replace existing steel materials can significantly reduce the weight of ships and warships, improve the maneuverability and carrying capacity of ships and warships, and reduce maintenance costs. 5000 series aluminum alloys are medium-strength aluminum alloys that cannot be strengthened by heat treatment and have good corrosion resistance and welding properties. However, the commonly used 5000 series aluminum alloys, such as 5005, 5052, 5083, etc., have the advantages of excellent corrosion resistance and welding properties, but their strength is still low, which cannot meet the requirements of lightweight development of ships and warships, and needs further improvement. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration.

[0004] The present invention adopts the following technical solution: A high-strength and lightweight marine mineral composite material for architectural decoration is prepared, comprising the following raw materials in parts by weight: 50 parts of basalt, 12-18 parts of coal gangue, 8-15 parts of iron ore tailings, 4-5 parts of calcite, 7.25-9.39 parts of silicon dioxide, 3.72-4.65 parts of aluminum oxide, 1.83-2.25 parts of calcium oxide, 1-3 parts of barium silicate, 0.47-0.59 parts of magnesium oxide, 0.91-1.26 parts of iron oxide, 0.08-0.15 parts of titanium oxide, 0.21-0.25 parts of potassium oxide, 0.32-0.39 parts of sodium oxide, 0.07-0.09 parts of arsenic oxide, and 0.05-0.07 parts of antimony oxide; The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing and ball-milling the raw materials except basalt according to the required weight to obtain powder; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1280-1480°C.

[0005] Furthermore, the chemical composition of the iron ore tailings is as follows in terms of mass percentage: Fe2O3: 50.28%, SiO2: 42.65%, Al2O3: 3.67%, ZnO: 1.2%, CuO: 0.86%, TiO2: 0.15%, and MgO: 1.19%.

[0006] Furthermore, in step 3, the firing is specifically controlled as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 620-660℃, and the kiln firing time is 2-3h; Decomposition and oxidation stage: the temperature in the kiln rises to 980-1020℃, and the kiln firing time is 3-5 hours; High temperature reduction stage: the temperature in the kiln rises to 1280-1480℃, and the kiln firing time is 7-8 hours; Stress relief stage: the temperature in the kiln is reduced to 540-560°C at a rate of 1.5°C / min, and the kiln is kept warm for 1-2 hours, then the temperature is increased to 780-820°C at a rate of 2°C / min, and the kiln is kept warm for 15-21 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0007] Furthermore, during the high temperature reduction stage, the carbon monoxide content is 4.2-4.8%, and the oxygen content is 1.5-1.8%.

[0008] Furthermore, during the stress relief stage, the carbon monoxide content is 5.0-5.5%, and the oxygen content is 1.0-1.2%.

[0009] Furthermore, the basalt is composed of the following raw materials in parts by weight: 20-30 parts of 5-8 mm basalt, 50-60 parts of 3-5 mm basalt, and 10-20 parts of 1-3 mm basalt.

[0010] Furthermore, in step 2, when the premix is ​​pressed, the vacuum press is controlled to work, and when the pressure reaches 1.0-1.2MPa, vacuuming is started, and the pressure is continuously increased to 1.5-1.8MPa, and then the pressure of the air compressor is maintained, and vacuuming is continued for 1-2h, and the premix is ​​pressed into shape and then sent to the kiln.

[0011] Furthermore, in step 1, the powder is ground to a particle size of 100-120 mesh.

[0012] From the above description of the present invention, it can be seen that compared with the prior art, the beneficial effects of the present invention are as follows: the present application limits the raw material composition of the mineral composite material, selects waste materials such as coal gangue, iron ore tailings, basalt, etc. as the main raw materials to improve the utilization rate of waste resources and greatly reduce costs, and further limits its preparation method, after the premix is ​​pressed and formed, it is placed at 1280-1480°C for firing, so that the iron ore tailings, calcite and coal gangue can expand and crack into smaller particles, so as to balance the shrinkage during the preparation of the mineral composite material, ensure the strength of the prepared offshore platform, and achieve the effect of lightweight; The firing process is specifically limited, and the firing temperature of each stage is strictly controlled to ensure that no cracks are generated inside the prepared mineral composite material, thereby improving the yield rate of the prepared mineral composite material. Among them, the process of the stress relief stage is specifically limited, and the stress inside the mineral composite material is eliminated through the cooling-heating-cooling process to prevent the incomplete release of the internal stress of the mineral composite material, which causes cracks in the finished product. The entire process is relatively simple, and the yield rate and dimensional stability of the mineral composite material are improved, thereby preventing it from being damaged or deformed during later processing and use, and it can be used to prepare offshore platforms; Specifically limit the pressing process of the green body to make it dense inside, greatly reduce the presence of pores, and prevent a large number of pores from forming inside during the subsequent firing process, which will affect the quality of the finished product of the mineral composite material and its subsequent use; When the premix is ​​prepared, the basalt is composed of particles of different sizes and is not crushed together with other raw materials, so that basalt particles of different sizes can be distributed in the prepared premix, so as to improve the lateral strength and longitudinal strength of the prepared mineral composite material and meet the use requirements of offshore platforms. DETAILED DESCRIPTION

[0013] The present invention is further described below through specific implementation modes.

[0014] A method for preparing a high-strength and lightweight marine mineral composite material for building decoration comprises the following raw materials in parts by weight: 50 parts of basalt, 12-18 parts of coal gangue, 8-15 parts of iron ore tailings, 4-5 parts of calcite, 7.25-9.39 parts of silicon dioxide, 3.72-4.65 parts of aluminum oxide, 1.83-2.25 parts of calcium oxide, 1-3 parts of barium silicate, 0.47-0.59 parts of magnesium oxide, 0.91-1.26 parts of iron oxide, 0.08-0.15 parts of titanium oxide, 0.21-0.25 parts of potassium oxide, 0.32-0.39 parts of sodium oxide, 0.07-0.09 parts of arsenic oxide, and 0.05-0.07 parts of antimony oxide.

[0015] The basalt is composed of the following raw materials in parts by weight: 20-30 parts of 5-8 mm basalt, 50-60 parts of 3-5 mm basalt, and 10-20 parts of 1-3 mm basalt.

[0016] The chemical composition of iron ore tailings is as follows by mass percentage: Fe2O3: 50.28%, SiO2: 42.65%, Al2O3: 3.67%, ZnO: 1.2%, CuO: 0.86%, TiO2: 0.15%, MgO: 1.19%.

[0017] The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials except basalt according to the required weight to obtain a powder with a particle size of 100-120 mesh; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into the molding mold, press it into shape, and then send it into the kiln to sinter it at 1280-1480℃. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 620-660℃, and the kiln firing time is 2-3h; Decomposition and oxidation stage: the temperature in the kiln rises to 980-1020℃, and the kiln firing time is 3-5 hours; High temperature reduction stage: the temperature in the kiln rises to 1280-1480℃, and the kiln firing time is 7-8 hours; Stress relief stage: the temperature in the kiln is reduced to 540-560°C at a rate of 1.5°C / min, and the kiln is kept warm for 1-2 hours, then the temperature is increased to 780-820°C at a rate of 2°C / min, and the kiln is kept warm for 15-21 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0018] Specifically, in step 2, when the premix is ​​pressed, the vacuum press is controlled to work, and when the pressure reaches 1.0-1.2MPa, vacuuming begins, and the pressure is continuously increased to 1.5-1.8MPa, and then the pressure of the air compressor is maintained, and vacuuming is continued for 1-2h, and the premix is ​​pressed into shape and then sent into the kiln.

[0019] In step 3, during the high-temperature reduction stage, the carbon monoxide content is 4.2-4.8%, and the oxygen content is 1.5-1.8%; during the stress relief stage, the carbon monoxide content is 5.0-5.5%, and the oxygen content is 1.0-1.2%.

[0020] Example 1 A method for preparing a high-strength and lightweight marine mineral composite material for building decoration comprises the following raw materials in parts by weight: 50 parts of basalt, 18 parts of coal gangue, 8 parts of iron ore tailings, 4 parts of calcite, 9.39 parts of silicon dioxide, 4.65 parts of aluminum oxide, 2.25 parts of calcium oxide, 1 part of barium silicate, 0.59 parts of magnesium oxide, 1.26 parts of iron oxide, 0.15 parts of titanium oxide, 0.25 parts of potassium oxide, 0.32 parts of sodium oxide, 0.07 parts of arsenic oxide, and 0.07 parts of antimony oxide.

[0021] The basalt is composed of the following raw materials in parts by weight: 20 parts of 5-8 mm basalt, 60 parts of 3-5 mm basalt, and 10 parts of 1-3 mm basalt.

[0022] The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials except basalt according to the required weight to obtain a powder with a particle size of 100 mesh; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1280°C. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 620℃, and the kiln firing time is 3h; Decomposition and oxidation stage: the temperature in the kiln is raised to 980°C and the kiln firing time is 5 hours; High temperature reduction stage: the temperature in the kiln is raised to 1280°C and the kiln firing time is 8 hours; Stress relief stage: the temperature in the kiln is reduced to 540°C at a rate of 1.5°C / min, and the kiln is kept at this temperature for 2 hours, then the temperature is increased to 780°C at a rate of 2°C / min, and the kiln is kept at this temperature for 21 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0023] Specifically, in step 2, when the premix is ​​pressed, the vacuum press is controlled to work, and when the pressure reaches 1.0 MPa, vacuuming begins, and the pressure is continuously increased to 1.5 MPa, and then the pressure of the air compressor is maintained, and vacuuming is continued for 2 hours, and the premix is ​​pressed into shape and then sent into the kiln.

[0024] In step 3, during the high-temperature reduction stage, the carbon monoxide content was 4.2%, and the oxygen content was 1.5%; during the stress relief stage, the carbon monoxide content was 5.0%, and the oxygen content was 1.2%.

[0025] Example 2 A method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration comprises the following raw materials in parts by weight: 50 parts of basalt, 12 parts of coal gangue, 15 parts of iron ore tailings, 5 parts of calcite, 7.25 parts of silicon dioxide, 3.72 parts of aluminum oxide, 1.83 parts of calcium oxide, 3 parts of barium silicate, 0.47 parts of magnesium oxide, 0.91 parts of iron oxide, 0.08 parts of titanium oxide, 0.21 parts of potassium oxide, 0.39 parts of sodium oxide, 0.09 parts of arsenic oxide, and 0.05 parts of antimony oxide.

[0026] The basalt is composed of the following raw materials in parts by weight: 30 parts of 5-8 mm basalt, 50 parts of 3-5 mm basalt, and 20 parts of 1-3 mm basalt.

[0027] The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials except basalt according to the required weight to obtain a powder with a particle size of 120 mesh; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1480°C. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 660℃, and the kiln firing time is 2h; Decomposition and oxidation stage: the temperature in the kiln is raised to 1020°C and the kiln firing time is 3 hours; High temperature reduction stage: the temperature in the kiln is raised to 1480°C and the kiln firing time is 7 hours; Stress relief stage: the temperature in the kiln is reduced to 560°C at a rate of 1.5°C / min, kept at that temperature for 1 hour, then raised to 820°C at a rate of 2°C / min, kept at that temperature for 15 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0028] Specifically, in step 2, when the premix is ​​pressed, the vacuum press is controlled to work, and when the pressure reaches 1.2 MPa, vacuuming begins, and the pressure is continuously increased to 1.8 MPa, and then the pressure of the air compressor is maintained, and vacuuming is continued for 1 hour, and the premix is ​​pressed into shape, and then sent into the kiln.

[0029] In step 3, during the high-temperature reduction stage, the carbon monoxide content was 4.8%, and the oxygen content was 1.8%; during the stress relief stage, the carbon monoxide content was 5.0%, and the oxygen content was 1.0%.

[0030] Example 3 A method for preparing a high-strength and lightweight marine mineral composite material for building decoration comprises the following raw materials in parts by weight: 50 parts of basalt, 15 parts of coal gangue, 12 parts of iron ore tailings, 4.5 parts of calcite, 7.82 parts of silicon dioxide, 4.18 parts of aluminum oxide, 2.05 parts of calcium oxide, 2 parts of barium silicate, 0.56 parts of magnesium oxide, 1.03 parts of iron oxide, 0.12 parts of titanium oxide, 0.24 parts of potassium oxide, 0.36 parts of sodium oxide, 0.08 parts of arsenic oxide, and 0.06 parts of antimony oxide.

[0031] The basalt is composed of the following raw materials in parts by weight: 25 parts of 5-8 mm basalt, 55 parts of 3-5 mm basalt, and 15 parts of 1-3 mm basalt.

[0032] The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials except basalt according to the required weight to obtain a powder with a particle size of 110 mesh; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1360°C. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 640℃, and the kiln firing time is 2.5h; Decomposition and oxidation stage: the temperature in the kiln is raised to 1000°C and the kiln firing time is 4 hours; High temperature reduction stage: the temperature in the kiln rises to 1360°C, and the kiln firing time is 7.5 hours; Stress relief stage: the temperature in the kiln is reduced to 550°C at a rate of 1.5°C / min, kept at that temperature for 1.5 hours, then raised to 800°C at a rate of 2°C / min, kept at that temperature for 18 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0033] Specifically, in step 2, when the premix is ​​pressed, the vacuum press is controlled to work, and when the pressure reaches 1.1 MPa, vacuuming begins, and the pressure is continuously increased to 1.6 MPa, and then the pressure of the air compressor is maintained, and vacuuming is continued for 1.5 hours, and the premix is ​​pressed into shape and then sent into the kiln.

[0034] In step 3, during the high-temperature reduction stage, the carbon monoxide content was 4.5%, and the oxygen content was 1.6%; during the stress relief stage, the carbon monoxide content was 5.2%, and the oxygen content was 1.1%.

[0035] The mineral composite materials prepared in Examples 1-3 were subjected to corresponding tests, and the specific results are shown in the table below.

[0036] Comparative Example 1 The raw material composition and preparation method are basically the same as those in Example 3, except that the preparation method comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials according to the required weight to obtain a premix with a particle size of 110 mesh; Step 2: pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1360°C. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 640℃, and the kiln firing time is 2.5h; Decomposition and oxidation stage: the temperature in the kiln is raised to 1000°C and the kiln firing time is 4 hours; High temperature reduction stage: the temperature in the kiln rises to 1360°C, and the kiln firing time is 7.5 hours; Stress relief stage: the temperature in the kiln is reduced to 550°C at a rate of 1.5°C / min, kept at that temperature for 1.5 hours, then raised to 800°C at a rate of 2°C / min, kept at that temperature for 18 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

[0037] Comparative Example 2 The raw material composition and preparation method are basically the same as those in Example 3, except that the preparation method comprises the following steps: Step 1, weighing, crushing, mixing, and ball-milling the raw materials according to the required weight to obtain a premix with a particle size of 110 mesh; Step 2: pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1360°C. The specific control of sintering is as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 640℃, and the kiln firing time is 2.5h; Decomposition and oxidation stage: the temperature in the kiln is raised to 1000°C and the kiln firing time is 4 hours; High temperature reduction stage: the temperature in the kiln rises to 1360°C, and the kiln firing time is 7.5 hours; Natural cooling stage: the temperature in the kiln is naturally cooled to room temperature to obtain the mineral composite material.

[0038] Table 1 Test data of various embodiments Test items <![CDATA[Density (g / cm 3 )]]> <![CDATA[Compressive strength (N / mm 2 )]]> <![CDATA[Modulus of elasticity (N / mm 2 )]]> Mohs hardness <![CDATA[Coefficient of expansion / 10 -6 ℃]]> Water absorption / % Example 1 2.6 270 1.45 7.2 3.5 0.30 Example 2 2.75 276 1.48 7.2 3.3 0.25 Example 3 2.9 283 1.52 7.5 3.1 0.18 Comparative Example 1 2.2 245 1.2 6.5 4.3 0.5 Comparative Example 2 2.1 185 0.95 5.1 5.6 1.2 It can be seen from the above table that the mineral composite material prepared in the present application has excellent strength and hardness, and low overall density, which can achieve a lightweight effect to provide the carrying capacity of the subsequently prepared marine platform.

[0039] The present application limits the raw material composition of the mineral composite material, selects waste materials such as coal gangue, iron ore tailings, basalt, etc. as the main raw materials to improve the utilization rate of waste resources and greatly reduce costs, and further limits its preparation method. After the premix is ​​pressed into shape, it is placed at 1280-1480°C for firing, so that the iron ore tailings, calcite and coal gangue can expand and crack into smaller particles to balance the shrinkage during the preparation of the mineral composite material, ensure the strength of the prepared offshore platform, and achieve the effects of lightweight and acid, alkali and corrosion resistance.

[0040] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. That is, equivalent changes and modifications made according to the application scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration, characterized in that: The invention comprises the following raw materials in parts by weight: 50 parts of basalt, 12-18 parts of coal gangue, 8-15 parts of iron ore tailings, 4-5 parts of calcite, 7.25-9.39 parts of silicon dioxide, 3.72-4.65 parts of aluminum oxide, 1.83-2.25 parts of calcium oxide, 1-3 parts of barium silicate, 0.47-0.59 parts of magnesium oxide, 0.91-1.26 parts of iron oxide, 0.08-0.15 parts of titanium oxide, 0.21-0.25 parts of potassium oxide, 0.32-0.39 parts of sodium oxide, 0.07-0.09 parts of arsenic oxide and 0.05-0.07 parts of antimony oxide; The preparation method thereof comprises the following steps: Step 1, weighing, crushing, mixing and ball-milling the raw materials except basalt according to the required weight to obtain powder; Step 2, mixing the prepared powder with basalt and stirring evenly to obtain a premix; Step 3, pour the premix into a molding mold, press it into shape, and then send it into a kiln to sinter it at 1280-1480°C.

2. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 1, characterized in that: The chemical composition of the iron ore tailings is as follows by mass percentage: Fe2O3: 50.28%, SiO2: 42.65%, Al2O3: 3.67%, ZnO: 1.2%, CuO: 0.86%, TiO2: 0.15%, MgO: 1.19%.

3. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 1, characterized in that: In step 3, the firing is specifically controlled as follows: Low temperature stage: the temperature in the kiln rises from room temperature to 620-660℃, and the kiln firing time is 2-3h; Decomposition and oxidation stage: the temperature in the kiln rises to 980-1020℃, and the kiln firing time is 3-5 hours; High temperature reduction stage: the temperature in the kiln rises to 1280-1480℃, and the kiln firing time is 7-8 hours; Stress relief stage: the temperature in the kiln is reduced to 540-560°C at a rate of 1.5°C / min, and the kiln is kept warm for 1-2 hours, then the temperature is increased to 780-820°C at a rate of 2°C / min, and the kiln is kept warm for 15-21 hours, and then naturally cooled to room temperature to obtain the mineral composite material.

4. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 3, characterized in that: During the high-temperature reduction stage, the carbon monoxide content is 4.2-4.8%, and the oxygen content is 1.5-1.8%.

5. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 3, characterized in that: During the stress relief stage, the carbon monoxide content is 5.0-5.5% and the oxygen content is 1.0-1.2%.

6. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 1, characterized in that: The basalt is composed of the following raw materials in parts by weight: 20-30 parts of 5-8 mm basalt, 50-60 parts of 3-5 mm basalt, and 10-20 parts of 1-3 mm basalt.

7. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 1, characterized in that: In step 2, when the premix is ​​pressed, the vacuum press is controlled to work. When the pressure reaches 1.0-1.2MPa, vacuuming begins, and the pressure is continuously increased to 1.5-1.8MPa. Then, the pressure of the air compressor is maintained, and vacuuming is continued for 1-2h. The premix is ​​pressed into shape and then sent into the kiln.

8. The method for preparing a high-strength and lightweight marine mineral composite material for architectural decoration according to claim 1, characterized in that: In step 1, the powder is ground to a particle size of 100-120 mesh.